2018
DOI: 10.1111/jfpp.13581
|View full text |Cite
|
Sign up to set email alerts
|

The effect on quality of pickled salted duck eggs using the novel method of pulsed pressure osmotic dehydration

Abstract: Salted eggs are a popular food or jardinière. In addition, this is the most traditional method to preserve eggs. A conventional method for pickling salted eggs is time‐consuming, strenuous, and difficult to control. The pulsed pressure osmotic dehydration (PPOD) technology uses pulsed pressure of osmotic solution to increase the pickling efficiency greatly. Previous reports have successfully applied PPOD for preparing salted hen eggs. However, there are no reports about the application of PPOD for pickling duc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…The sensory evaluation of cooked salted duck eggs was on the basis of the method of Yuan et al. (2018) . Fifty panelists (students and teachers from the College of Food Science & Technology Nanchang University) were trained in the sensory evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…The sensory evaluation of cooked salted duck eggs was on the basis of the method of Yuan et al. (2018) . Fifty panelists (students and teachers from the College of Food Science & Technology Nanchang University) were trained in the sensory evaluation.…”
Section: Methodsmentioning
confidence: 99%
“…This process resulted in a significantly higher salt content in salted eggs after 48 h, solidified egg yolks, oil exudation, and gritty structures. Yuan et al. (2018) found that pulsed pressure increased the exudation rate of salted egg yolks oil and concluded that pulsed pressure facilitated gas and salt penetration by changing the microstructure of the shells and membranes as well as the distribution of water.…”
Section: Rapid Pickling Technologies For Pickled Eggsmentioning
confidence: 99%
“…Pulsed pressure osmotic dehydration (PPOD) is a new technology used to improve the mass transfer and quality attributes of different food products [ 9 , 13 , 14 , 15 , 16 ]. PPOD uses high pressure to improve the penetration of the solvent into the product and the low pressure to release the microbubbles from the product tissue into the solution [ 9 ].…”
Section: Introductionmentioning
confidence: 99%